Human Cytomegalovirus: A culprit of infection in renal and bone marrow transplant recipients in Malaysia / Mohd Fahmi Mastuki ... [et al.] - Mastuki, Mohd Fahmi; Sinniah, Mangalam; Mohamed Shakrin, Nik Noorul Shakira; Masri, Siti Norbaya; Mohd Taib, Niazlin (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Human cytomegalovirus (HCMV) infection may cause substantial morbidity and mortality after renal and bone marrow transplantation. The aims of this study were to determine the incidence of HCMV infection in renal and bone marrow transplant recipients and to investigate its associations with HCMV disease, gender and races. This analysis involved 200 blood samples from renal and bone marrow transplant recipients from January 2011 to June 2012. The overall incidence of HCMV infection in the study group was 70.5% (141/200) where renal and bone marrow transplants account for 78.0% (78/100) and 63.0% (63/100), respectively. The incidence of HCMV infection in renal transplantation differed significantly by sex (p<0.05) where it was higher in males (78.2%) than in females (21.8%) but there was no statistically significant difference by sex in bone marrow transplantation in which males and females account for 47.6% and 52.4% respectively. The incidence of HCMV infection was not significantly different (p>0.05) by races in both transplantation types. The percentages are as follows: 45% (Malay), 24% (Chinese), 17% (Indian) and 15% (other indigenous races) in renal transplantation while 75% (Malay), 3% (Chinese), 8% (Indian) and 13% (other indigenous races) in bone marrow transplantation. The most seen symptoms were fever followed by generalised lethargy and headache. This study has shown that HCMV viral load has no significant association between age, gender, races and HCMV disease. Treatment with anti-HCMV therapy results in decline in HCMV load, usually to undetectable.